Extracranial–intracranial bypass in medial sphenoid ridge meningioma associated with severe stenosis of the intracranial segments of the internal carotid artery: A case report. Issue 24 (June 2018) - Huang, Yabo; Wang, Zhong; Han, Qingdong
Abstract: Rationale: Tumor resection and extracranial-intracranial bypass concerning medial sphenoid ridge meningioma associated with severe stenosis of the internal carotid artery (ICA) of intracranial segments has been rarely presented. Effective treatment as to the complex lesions may be complicated. Tumor resection and cerebrovascular protection should be both taken into consideration. Patient concerns: We presented one case of medial sphenoid ridge meningioma associated with severe stenosis of the internal carotid artery of intracranial segments. The patient suffered hyperthyroidism, mirror-image dextrocardia and congenital heart disease atrial septal defect simultaneously. Diagnoses: Before the neurosurgical treatment, the colleagues of department of cardiac surgery, anesthesiology and respiratory medicine agreed on our plan of resecting the tumor following the comprehensive evaluation of basal clinical conditions in the patient. For reducing the bleeding intraoperatively, the interventional branch performed digital subtraction angiography(DSA) and found collateral anastomosis between the supplying vessels of left middle meningeal arteries and anterior choroid arteries. No preoperative interventional embolization was determined considering the risk of cerebral ischemia. Interventions: The following subtotal resection of medial sphenoid ridge meningioma and left extracranial-intracranial bypass were carried out. Additionally, ipsilateral decompressive craniectomy was done. Post-operative imaging Computed tomography (CT), Computed tomography angiography (CTA) and Transcranial Doppler (TCD) indicated subtotal resection of tumor and bypass patency. Outcomes: The patient was discharged with the right limbs of muscle strength of grade IV. The muscle strength of the patient returned to grade V after 6 months of follow-up. Lessons: Comprehensive treatment of tumor resection and extracranial-intracranial bypass concerning medial sphenoid ridge meningioma associated with severe stenosis of the internal carotid artery of intracranial segments is effective.